Local compartment changes and regulatory landscape alterations in histone H1-depleted cells. Issue 1 (December 2015) - Geeven, Geert; Zhu, Yun; Kim, Byung; Bartholdy, Boris; Yang, Seung-Min; Macfarlan, Todd; Gifford, Wesley; Pfaff, Samuel; Verstegen, Marjon; Pinto, Hugo; Vermunt, Marit; Creyghton, Menno; et al.
Abstract Background Linker histone H1 is a core chromatin component that binds to nucleosome core particles and the linker DNA between nucleosomes. It has been implicated in chromatin compaction and gene regulation and is anticipated to play a role in higher-order genome structure. Here we have used a combination of genome-wide approaches including DNA methylation, histone modification and DNase I hypersensitivity profiling as well as Hi-C to investigate the impact of reduced cellular levels of histone H1 in embryonic stem cells on chromatin folding and function. Results We find that depletion of histone H1 changes the epigenetic signature of thousands of potential regulatory sites across the genome. Many of them show cooperative loss or gain of multiple chromatin marks. Epigenetic alterations cluster to gene-dense topologically associating domains (TADs) that already showed a high density of corresponding chromatin features. Genome organization at the three-dimensional level is largely intact, but we find changes in the structural segmentation of chromosomes specifically for the epigenetically most modified TADs. Conclusions Our data show that cells require normal histone H1 levels to expose their proper regulatory landscape. Reducing the levels of histone H1 results in massive epigenetic changes and altered topological organization particularly at the most active chromosomal domains. Changes in TAD configuration coincide with epigenetic landscape changes but not with transcriptional output changes, supporting the emerging concept that transcriptional control and nuclear positioning of TADs are not causally related but independently controlled by the locally associatedtrans -acting factors.